Service export and economic growth in the selected developing Asian countries - Kaliappan, Shivee Ranjanee; Ahmad, Siti Asiah; Ismail, Normaz Wana (Faculty of Economics and Management, Universiti Putra Malaysia, 2017)
Services trade is regarded as a new source of income, especially for developing countries. Even though services trade only represent 20.2 per cent (2010) to total world trade, interestingly, recent trend shows that the share for developing countries in services trade increased to 32 per cent (2010) as compared to only 20 per cent in 1990. Moreover, the share of service export to total exports also increased from 18 per cent in 1990 to 30 per cent in 2010. Although, most of the developing countries are still net importers of services, there is a widespread belief among scholars and policy makers that there is great potential for services exports to grow further as new source of income for developing countries. Thus, the main purpose of this study is to examine the impact of service export on economic growth using panel dynamic OLS (DOLS) in selected Asian countries (i.e. China, Hong Kong, South Korea, India, Iran, Indonesia, Malaysia, Philippines, Singapore, Thailand, Kuwait, Saudi Arabia and Turkey). Annual data covering the period from 1985 to 2012 was utilized. The findings indicate that all of the macroeconomic variables tested are co-integrated in the long run. Service export also has a significant and positive impact on economic growth. The findings implies that the Asian developing countries should focus on formulating appropriate policy measures to enhance the performance of services sector and service export to stimulate the economic growth.